Individual genetic and genomic research results and the tradition of informed consent: exploring US review board guidance. Issue 7 (23rd February 2012) - Simon, Christian; Shinkunas, Laura A; Brandt, Debra; Williams, Janet K
Abstract : Background: Genomic research is challenging the tradition of informed consent. Genomic researchers in the USA, Canada and parts of Europe are encouraged to use informed consent to address the prospect of disclosing individual research results (IRRs) to study participants. In the USA, no national policy exists to direct this use of informed consent, and it is unclear how local institutional review boards (IRBs) may want researchers to respond. Objective and methods: To explore publicly accessible IRB websites for guidance in this area, using summative content analysis. Findings: Three types of research results were addressed in 45 informed consent templates and instructions from 20 IRBs based at centres conducting genomic research: (1) IRRs in general, (2) incidental findings (IFs) and (3) a broad and unspecified category of 'significant new findings' (SNFs). IRRs were more frequently referenced than IFs or SNFs. Most documents stated that access to IRRs would not be an option for research participants. These non-disclosure statements were found to coexist in some documents with statements that SNFs would be disclosed to participants if related to their willingness to participate in research. The median readability of template language on IRRs, IFs and SNFs exceeded a ninth-grade level. Conclusion: IRB guidance may downplay the possibility of IFs and contain conflicting messages on IRR non-disclosure and SNF disclosure. IRBs may need to clarify why separate IRR and SNF language should appear in the same consent document. The extent of these issues, nationally and internationally, needs to be determined.